Improving Students' Reading Ability Using Picture Story Books in Indonesian Courses - Iram Maa; Yulanti S. Mooduto (Journal of Education Review Provision, 2023)
The goal of this study is to develop students' fluency in reading aloud from illustrated storybooks about Indonesian culture and history in Class II at SDN 01 Duhiadaa in the Pohuwato Regency. The research design is an action study in the classroom, and the sample size is 22 students in Grade 2. This study was conducted in cycles, with each cycle including the phases of planning, carrying out the plan, monitoring the results, and reflecting on the study's findings. According to the results of this study, pupils' proficiency in reading aloud is low across the board in Indonesian courses. Students' low reading aloud skill at the time of initial observation indicates this, with 50% falling into the bad category, 68.18% falling into the fairly good category, and 95.45% rising to the very good category in the second cycle. Students in class II at SDN 1 Duhiadaa, Pohuwato Regency, can benefit from the use of picture story books as a form of learning media to enhance their fluency in reading aloud. After the second cycle of the second meeting, the researcher called it quits because they had met the 80% performance indicator they had set out to achieve.